The Effects Of Global Economic Crisis of 2008 to Financial Statements and Liquidity Ratios Which Companies are Settled In BIST Energy Sector (2005-2013 Term Review) - Kendirli, Selcuk; Cankaya, Muhammet; Cagatay, Altug (Journal of Economic Development, Environment and People, 2017)
Abstract. Aim of this study is to compare and analyze whether the 2008 global economic crisis affected the balance of the energy companies which are listed in the İstanbul Stock Exchange and have shown continuity in 2005-2013 period by using a variety of analyzing methods. Companies that demonstrate continuity between the years 2005-2013 were not assessed in this study. Horizontal and vertical analyses were made on the financial statements of the companies which are evaluated and liquidity ratios were assessed. As a result of the analysis the companies have been found to be affected to different degrees by the crisis.